(3JPcQI GdabgGAs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3adGM Hf Ydj GdcQOjs)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje (B" (3cJGH GdUdGI (B" (3hajg ebGUO(B: (3GdChd(B: (3aj GdebOeGJ, hajg aUhd(B: (3GdChd(B: (3aj CYOGOgG(B. (3ebOeI(B: (3GdUdGI dZI(B: (3GdOYGA, hTQYG(B: (3PGJ GdQchY hGdSLhO, hgj ef Cge GdYHGOGJ (B...s
(3BNQgG (B:s
.... (3GSJUHGM HGdOgf GdfLS JMJ GdSeGA dG JMJ GdXdGd HNdGa eG fLGSJg PGJjI cTMe GdejJI hddTGaYj bhdGf GWdGb GdefY hEWdGb GdLhGR aj GdXdGd hYOe PGJj GdfLGSI(B.. (3Je cJGH GdUdGIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B2/227s
(3cTa GdXfhf (B1\390s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis